Self-control and aggression versatility: moderating effects in the prediction of delinquency and conduct disorder among youth - Pechorro, Pedro (2021)
An individual’s capacity for self-control is an important factor when considering the link between aggression and delinquency outcomes. The aim of the present study is to examine the possible role of self-control as a moderator of the aggression-antisociality/delinquency link among a sample of 567 youth (M = 15.91 years, SD = .99 years, age range = 14–18 years) from Portugal. Results indicated that self-control significantly moderates four different forms and functions of aggression – proactive overt, proactive relational, reactive overt, and reactive relational – in models simultaneously predicting delinquency and conduct disorder outcomes. We encourage multifaceted study of aggression as inherent in the Peer Conflict Scale-20 to articulate the ways that various forms of aggression unfold into clinical conduct problems.